Investigação do efeito do envio automático de alertas ao paciente com HIV/AIDS por meio de mensagem de texto para celular na adesão ao tratamento antiretroviral - Costa, Thiago Martini da [UNIFESP] (2011)
Objective: To assess if SMS automatic sending increases the adherence antiretroviral drug-based treatment regimens. Methods: The web system HIVAS was projected according to software engineering cascade model. It was conducted two experiments: Experiment 1, a randomized controlled trial with woman living with HIV/AIDS to assess the effects of SMS on adherence to antiretroviral therapy; Experiment 2, a transversal study with data extracted from two electronic health recorders of 4 outpatient clinics to assess the effects of SMS on non-attendance rates. On Experiment 1 adherence of participants allocated to receive SMS, called intervention (n=8), and to not receive SMS, labeled control (n=13), was measured during 4 months by self-reported adherence, pill counting, and microelectronic monitoring (MEMS). On Experiment 2, the incidence of non-attendance when a SMS reminder was sent to the appointment, labeled intervention (n=7,890), was compared to the incidence of non-attendance when no SMS reminder was sent, labeled control (n=21,124). Results: The HIV Alert System (HIVAS) was developed over 7 months during 2008 and 2009. On Experiment 1, during the 4-month study period, the number and percentage of participants from both control and intervention groups that achieved adherence levels to antiretroviral therapy exceeding 95%, were respectively: 11 (84.62%) and 8 (100.00%) to self-reported adherence method; 5 (38.46%) and 4 (50.00%) to pill counting method; and 6 (46.15%) and 6 (75.00%) to micro-electronic monitoring. On Experiment 2, the average non-attendance rate to appointments without previous SMS was 25.57%, while average non-attendance rate to appointments with previous SMS was 19.42%. Conclusion: SMS messaging has demonstrated potential in helping patient adherence to therapy. Brazilian women living with HIV/AIDS who received SMS stated that the messages were reminders, incentives and signs of affection by the health clinic for their, a marginalized population. Beside this, it was observed a statistically significant reduction on the incidence of non-attendance due to SMS messages. The development of HIVAS was the less difficulty phase in the project, emphasizing the feasibility of SMS incorporation to help clinical practice.